Sport, rules, and values : philosophical investigations into the nature of sport - McFee, Graham (Routledge, 2004)
Sport, Rules and Values presents a philosophical perspective on some issues concerning the character of sport. Throughout, the presentation is rich in concrete cases from sporting situations, including cricket, baseball, American football, and.